Impacto periodístico digital en la educación de jóvenes universitarios del cantón Quevedo año 2021 - Arellano Litardo, Kimberly Janeth (2021)
The present investigative work consists of identifying the impact of digital journalistic media on young university students belonging to the Canton Quevedo, located in the province of Los Ríos, whose main objective is to identify the use of social networks with the propagation of verified or fake information that violates events and alarm society. The research was developed with an analytical and descriptive character. This research work undertakes the development of the theoretical foundation, which was carried out in search of the variables in the different possible sources, in order to achieve a correct definition and from there with the development of the case. Chapter number one details the definition and concepts of everything thar includes cyberjournalism, education in social networks, digital journalistic media and the modalities in which they impart information. In chapter number two we highlight the case study in the investigative work detailing the possible situations that promote digital content, garbage or misnamed entertainment that contribute to media lynching and / or unfavorable for educational consumption, we continue with the possible solutions for counteract the consumption of vulgar, false and destructive content that affects susceptibilities, in addition to the conclusions and recommendations pertaining to the investigation. The design of this project is that the information on social networks must be verifield before sharing it and consuming these fallacies as the only truth, avoid contributing power to all the publications that are disseminated on the internet, promoting media sities and/ or show-goers involves us In an unfavorable vicious circle for society, promulgating hatred or repudiation through different free social applications that we manage with a personal profile, focus on consuming information from local media established by journalists and social communicators who carry out their work professionally to keep informed the community and the nation.